ANALYSIS OF STUDENTS' CREATIVE THINKING ABILITY ON ENVIRONMENTAL POLLUTION MATERIALS IN CLASS VII SMP PANGERAN ANTASARI - Silfi Indriani; Hasruddin Hasruddin; Waluyo Waluyo (UNIVERSITAS NEGERI MEDAN, 2022)
This study aims to: (1) describe students' creative thinking skills on Environmental Pollution material at Prince Antasari Middle School; (2) to find out the description of students' creative thinking skills on Environmental Pollution material at Prince Antasari State Junior High School; and (3) knowing the percentage of creative thinking ability on each indicator of creative thinking ability. The type of research conducted in this research is descriptive research using a mixed methods approach and non-experimental research design. The data collection stage uses a test instrument that contains description questions for creative thinking skills and uses a questionnaire for the student learning process. The sampling technique used is total sampling by taking samples of two classes. The subjects of this study were seventh grade students of Prince Antasari Middle School, totaling 73 students. The samples in this study were 38 students in class VII-1 and class VII-2, totaling 35 students. The results showed quite good with 31 students (42.5%), followed by good criteria with 30 students (41.1%). , then less well with 6 students (8.2%), and there are only 2 students (2.7%). The conclusion of this study shows that students' creative thinking abilities are in the category of creative enough with a learning process that has quite good criteria